Effect of salt stress on the parasitism of Meloidogyne enterolobii in cowpea (Research, Society and Development, 2021)
Cowpea, Vigna unguiculata (L.) Walp, is a very important Fabaceae in the diet of families in the northeast region of Brazil. This plant species is among the different cultures affected by the root-knot nematode. In this region, in addition to phytonematodes, another condition that affects cowpea productivity is salinity, one of the main abiotic limiting factors. The cultivar Pitiúba, however, has good adaptability to salt stress conditions. However, information on the behavior of root-knot nematodes in an environment with high levels of salinity for this crop is still scarce. Based on the above, the objective of this work was: 1) to evaluate the hatchability of J2 of Meloidogyne enterolobii in 100mM NaCl solution; 2) evaluate the motility and infectivity of J2 of M. enterolobii in saline solution at the levels of 0, 25, 50, 75, 100, 125, 150, 175, 200, 300, and 400mM; 3) to investigate the impairment of the development of M. enterolobii in cowpea Pitiúba under irrigation with NaCl solution at 100mM. It was found that J2 hatching, motility, and infectivity of juveniles of M. enterolobii were not affected by the levels of salinity tested in vitro. In Pitiúba, irrigation with 100 mM saline solution considerably affected the development of juveniles of the pathogen in the roots.